Adopsi climate smart agriculture dalam mendukung peningkatan produktivitas kentang: kasus program ICARE di Kabupaten Garut: Adoption of climate-smart agriculture to support increased potato productivity: a case study of the ICARE program in Garut Regency - Rigan Diaz Algifari; Asep Najmudin; Edeng Hidayat; Yayah Haeriah (COMPOSITE : Jurnal Ilmu Pertanian, 2026)
Climate change has become one of the major challenges in potato farming development. One of the adaptation strategies promoted by the Indonesian government is the implementation of Climate Smart Agriculture (CSA). This study aimed to analyze the level of CSA and examine its implementation in supporting the improvement of potato farming productivity in Garut Regency, Indonesia. The study employed a mixed-methods approach using a concurrent embedded case study design. The respondents consisted of five farmers participating in the ICARE Program, selected through a census technique. Quantitative data were collected through field observations, questionnaires, and actual productivity data before and after CSA implementation, and were analyzed descriptively. Qualitative data were obtained through semi-structured interviews and analyzed using thematic analysis. The results showed that the cumulative adoption level of CSA innovation components was classified as high, with a score of 495 (94.29%). The average potato productivity increased from 14.6 tons/ha to 34.0 tons/ha following CSA implementation. The main factors supporting successful adoption included extension assistance, access to information, the observable benefits of innovation, and farmers' expectations of increased farm profitability. Meanwhile, the main constraints to CSA implementation included limited financial resources, restricted access to certified seeds, and the need to adapt the technology to local agroecosystem conditions. These findings indicate that the successful implementation of CSA is determined not only by technology adoption but also by effective extension services, farmer learning processes, and institutional strengthening, all of which contribute to the sustainable improvement of potato farming productivity.